Vitamin K Status, Warfarin Use, and Arterial Stiffness in Heart Failure. Issue 2 (February 2019) - Hashmath, Zeba; Lee, Jonathan; Gaddam, Swetha; Ansari, Bilal; Oldland, Garrett; Javaid, Khuzaima; Mustafa, Anique; Vasim, Izzah; Akers, Scott; Chirinos, Julio A.
Abstract : Large artery stiffening contributes to the pathophysiology of heart failure (HF) and associated comorbidities. MGP (matrix Gla-protein) is a potent inhibitor of vascular calcification. MGP activation is vitamin K–dependent. We aimed (1) to compare dp-ucMGP (dephospho-uncarboxylated MGP) levels between subjects with HF with preserved ejection fraction (HFpEF) and HF with reduced ejection fraction (HFrEF) and subjects without HF; (2) to assess the relationship between dp-ucMGP levels and arterial stiffness; and (3) to assess the relationship between warfarin use, dp-ucMGP levels, and arterial stiffness in HF. We enrolled 348 subjects with HFpEF (n=96), HFrEF (n=53), or no HF (n=199). Carotid-femoral pulse wave velocity, a measure of large artery stiffness, was measured with arterial tonometry. Dp-ucMGP was measured with ELISA. Dp-ucMGP levels were greater in both HFrEF (582 pmol/L; 95% CI, 444–721 pmol/L) and HFpEF (549 pmol/L; 95% CI, 455–643 pmol/L) compared with controls (426 pmol/L; 95% CI, 377–475 pmol/L; ANCOVA P =0.0067). Levels of dp-ucMGP were positively associated with carotid-femoral pulse wave velocity (standardized β, 0.31; 95% CI, 0.19–0.42; P <0.0001), which was also true in analyses restricted to patients with HF (standardized β, 0.34; 95% CI, 0.16–0.52; P =0.0002). Warfarin use was significantly associated with carotid-femoral pulse wave velocity (standardized β, 0.13; 95% CI, 0.004–0.26; P =0.043), but this relationship was eliminated after adjustment for dp-ucMGP. In conclusion, levels of dp-ucMGP are increased in HFpEF and HFrEF and are independently associated with arterial stiffness. Future studies should investigate whether vitamin K supplementation represents a suitable therapeutic strategy to prevent or reduce arterial stiffness in HFpEF and HFrEF.